Nardo, Ed., The French Revolution - Blanke, David (Teaching History: A Journal of Methods, 2000)
The French Revolution certainly qualifies by any standard as a "Turning Point in World History." Its inclusion within the Greenhaven Press series of the same name should distress no one. Yet, identifying exactly what "turned" and why, remains at the heart of an analysis that began with the calling of the Estates General in 1789 and continues to this day. This volume's Foreword (a mere two pages) and Introduction, which are uncredited, go far to define the Revolution as a "turning point," and give a good narrative account of events, but do little to direct readers to any blended answers to these more pivotal questions.